Reaction condition-dependent divergent synthesis of spirooxindoles and bisoxindoles. Issue 14 (24th May 2021) - Chen, Guo-Shu; Fang, Yu-Bo; Ren, Zhi; Tian, Xu; Liu, Yun-Lin
Abstract : DABCO-catalyzed divergent transformations of isatin-derived MBH carbonates leading to either spirocyclopentene oxindoles, spirocyclopentadiene 2-oxindoles or bisoxindoles are described. Abstract : The ability to access structurally diverse and complex compounds efficiently and economically from readily available starting materials is an important goal in organic synthesis and medicinal chemistry. Herein, DABCO-catalyzed reactions between isatin-derived MBH carbonates and 3-formylchromones selectively leading to either benzopyrone fused spirocyclopentene oxindoles or spirocyclopentadiene 2-oxindoles incorporating a 2-hydroxybenzoyl moiety are described. Interestingly, in the absence of 3-formylchromones, the first synthesis of bisoxindoles containing highly functionalized tri - and tetra -substituted alkene groups can be achieved using the same catalytic system. In this case, the in situ generated tert -butyl carbonate anion (BocO − ), which is usually produced as a precursor of the tert -butoxide anion ( t BuO − ) or as waste, could be finely merged into the products as an efficient nucleophilic partner. Importantly, this tunable approach not only represents a rare example of isatin-derived MBH carbonate-based α-regioselective [3 + 2] annulations, but also constitutes the first intermolecular allylic alkylation reaction between two isatin-derived MBH carbonate molecules.